2022
DOI: 10.1155/2022/8503239
|View full text |Cite|
|
Sign up to set email alerts
|

Design and Application of Artificial Intelligence Technology-Driven Education and Teaching System in Universities

Abstract: In recent years, many colleges and universities have been experimenting and exploring the evaluation of education and teaching system and have achieved certain results. In order to understand the quality of education and teaching system in colleges and universities, to improve the school conditions, and to promote the reform of teaching management, methods and means of evaluating the quality of education and teaching system in general higher education institutions are needed. Modern university education and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…AI is also used for other tasks, such as organizing the sequence of curriculum in pacing guides for future groups of students and also designing instruction. Zhang (2022) described how designing an AI teaching system of talent cultivation and using the digital affordances to establish a quality assurance system for practical teaching, provides new mechanisms for the design of university education systems. In developing such a system, Zhang found that the stability of the instructional design, overcame the drawbacks of traditional manual subjectivity in the instructional design.…”
Section: Managing Student Learningmentioning
confidence: 99%
“…AI is also used for other tasks, such as organizing the sequence of curriculum in pacing guides for future groups of students and also designing instruction. Zhang (2022) described how designing an AI teaching system of talent cultivation and using the digital affordances to establish a quality assurance system for practical teaching, provides new mechanisms for the design of university education systems. In developing such a system, Zhang found that the stability of the instructional design, overcame the drawbacks of traditional manual subjectivity in the instructional design.…”
Section: Managing Student Learningmentioning
confidence: 99%
“…A study conducted by (Zhang, 2022) aims to propose and evaluate an AI-driven approach for the evaluation and adjustment of online higher education and teaching systems. The aim is to address the current challenges faced by colleges and universities in meeting the demands of society in terms of engineering practice ability, innovation ability, and international competitiveness.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Again addressing RQ1, the multiple affordances of GenAI-facilitated pedagogical innovation in HE are documented in a number of publications, such as Archibald et al ( 2023), Chang et al (2022), Cox et al (2022), Razia et al (2022), Zhang (2022), andZhou (2022), which detail advantages such as content generation for lectures or assessments, assisted data analysis, and greater administrative efficiency. Ghnemat et al (2022) take a similar approach and make a convincing call for further investigation into AI-based learning.…”
Section: Implications Of Genai For He Instructionmentioning
confidence: 99%